The Brazilian conditional cash transfer program and cardiovascular mortality: a data linkage study. (30th September 2020) - Pescarini, J M; Craig, P; Allik, M; Amorim, L; Ali, M S; Smeeth, L; Barreto, M L; Leyland, A; Aquino, E M L; Katikireddi, S V
Abstract: Background: Conditional cash transfer programmes (CCTs) make monetary transfers to poor families conditional on health check-ups and/or education attendance. CCTs have been key in reducing poverty and improving child and maternal health in low- and middle-income countries (LMICs) but their impact on cardiovascular mortality have not been studied. We aimed to evaluate the effect of the CCT Bolsa Familia Program (BFP) on premature all-cause and cardiovascular mortality in Brazil. Methods: The 100 Million Brazilian Cohort combined information about individuals applying for social programmes, the BFP and mortality data. We analysed ∼8 million individuals aged 30-69 who applied from 2011 to 2015. We calculated inverse probability weights (IPW) for the probability to receive BFP based on baseline observed characteristics (age, education, race, geographical location, household characteristics and year of application). Individuals were followed until they reached 70 years of age, died by any cause, or until 31st Dec 2015. We used Poisson regression (with person-years as the offset) and IPWs to compare BFP recipients to a comparable control population. Females and males were analysed separately. Results: By following individuals for up to 4 years, 43, 562 deaths by all-causes occurred among 4, 197, 658 females and 69, 209 deaths among 3, 672, 393 males. Female BFP beneficiaries had approximately 60% lower all-cause mortality (IRR=0.40;95%CI=0.37-0.42) and CVD mortality (IRR=0.42;95%CI=0.37-0.47) than non-beneficiaries. Males who are BFP beneficiaries had ∼50% lower all-cause (IRR=0.53;95%CI=0.52-0.55) and 60% lower cardiovascular mortality (IRR=0.40;95%CI=0.38-0.42) than non-beneficiaries. Conclusions: BFP, the world's largest CCT, may substantially decrease premature mortality. CCTs might have important implications for the growing burden of non-communicable diseases, with impacts potentially due to improved nutrition, socioeconomic conditions and improved primary care access. Key messages: The Brazilian CCT, a widely recognized programme for poverty alleviation, have showed to be associated with lower overall and cardiovascular premature mortality in both women and men. Other countries, particularly LMICs, may learn from the health benefits of CCTs and should consider its potential large effect on mortality when planning austerity policies.